Transient RNA-DNA hybrids are required for efficient double-strand break repair - Ohle, Corina; Tesorero, Rafael; Schermann, Géza; Dobrev, Nikolay; Sinning, Irmgard; Fischer, Tamás (Cell, 2016)
RNA-DNA hybrids are a major internal cause of DNA damage within cells, and their degradation by RNase H enzymes is important for maintaining genomic stability. Here, we identified an unexpected role for RNA-DNA hybrids and RNase H enzymes in DNA repair. Using a site-specific DNA double-strand break (DSB) system in Schizosaccharomyces pombe, we showed that RNA-DNA hybrids form as part of the homologous-recombination (HR)-mediated DSB repair process and that RNase H enzymes are essential for their degradation and efficient completion of DNA repair. Deleting RNase H stabilizes RNA-DNA hybrids around DSB sites and strongly impairs recruitment of the ssDNA-binding RPA complex. In contrast, overexpressing RNase H1 destabilizes these hybrids, leading to excessive strand resection and RPA recruitment and to severe loss of repeat regions around DSBs. Our study challenges the existing model of HR-mediated DSB repair and reveals a surprising role for RNA-DNA hybrids in maintaining genomic stability.
Gesehen am 03.07.2020